Chemically fueled covalent crosslinking of polymer materials. Issue 14 (29th January 2019) - Zhang, Borui; Jayalath, Isuru M.; Ke, Jun; Sparks, Jessica L.; Hartley, C. Scott; Konkolewicz, Dominik
Abstract : Non-equilibrium covalently crosslinked hydrogels are synthesized using carbodiimide fueled coupling of carboxylic acids to anhydrides which eventually dissipate by hydrolysis. Abstract : Transiently crosslinked dynamic polymer networks are developed, using carbodiimide hydration to link carboxylic acids as anhydrides. From aqueous polymer solutions, non-equilibrium hydrogels are transiently formed, which dissolve upon anhydride hydrolysis. The materials can be refueled using a subsequent injection of carbodiimide. The gels exhibit higher storage moduli compared to transient supramolecular gels as a result of their covalent crosslinks.